Recurrent Epileptic Auras As a Presenting Symptom of Alzheimer’s Disease - Sarkis, Rani A.; Willment, Kim C.; Gale, Seth A.; Dworetzky, Barbara A. (Frontiers in Neurology, 2017)
Seizures are a common co-morbidity during the course of Alzheimer’s Disease (AD) and in a subset of patients may be one of the presenting symptoms. In this case series we highlight three patients with recurrent medically refractory epileptic auras whose work up ultimately lead to the diagnosis of AD. All 3 patients underwent prolonged EEG, serial neuropsychological testing, FDG-PET, CSF AD biomarkers and MRI. CSF biomarkers were particularly helpful in two cases. These cases highlight the importance of having a high index of suspicion for AD in new onset “idiopathic” epilepsy in the elderly.